Structural Interpretation of 3D Seismic Data of a Passive Rift Margin: A Case Study of Bellatrix Basin (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The Bay of Biscay is considered France’s most prospective offshore region, but a complex geodynamic history has so far hindered its development. The landward side of the Parentis Basin has significant oil shows in late Barremian Limestones and early middle Jurassic dolomites. The offshore extension however has a thicker depocentre with a contrasting burial history resulting in plays more difficult to define – dampening drilling enthusiasm to date. Although the basin remains poorly understood this study has found the evidence of petroleum potential. Due to somewhat limited well control the risk remains a significant factor in further exploration. A maturity window in the Early Cretaceous has suggested targeting of more subtle structural and robust stratigraphic intervals on the footwall block could potentially be prospective. This study would recommend a rigorous 3D basin modeling project (outside the scope of this study) and acquisition of minimum 2D seismic between the existing block and onshore Parentis fields – this would allow better understanding of the transitional structure and subsequently the disparity in burial history/charge timing.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 89-102